Beyond the Post-Colonial Gaze: Recognizing Pachamama - Furia, Paolo (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2026)
Landscapes are the skin of the Earth: they reflect the environmental and cultural well-being of human communities, especially in an age of climate crisis. Focusing on Peru's Huancavelica region, Beyond the Post-Colonial Gaze affirms the philosophical value of Andean cosmovision, challenging dominant aesthetic paradigms shaped by tourism and media. The book advances an original onto-phenomenological theory of landscape, bridging prevailing spatial models with insights from diverse disciplines in a transdisciplinary and innovative framework.